Unraveling Green Extractivism: The Case of Nickel Downstreaming in the Indonesia Morowali Industrial Park - Bintang Corvi Diphda; Reza Triarda (Universitas Islam Negeri Madura, 2026)
The global energy transition has increased demand for critical minerals used in electric vehicle batteries, positioning nickel as a strategic resource. In Indonesia, this demand is linked to a state-led downstreaming agenda centered on the Indonesia Morowali Industrial Park (IMIP), a major hub for nickel processing. This article examines how sustainability narratives are used to drive extractive expansion in IMIP. It adopts a qualitative single-case study design and uses a desk review of policy documents, corporate reports, gray literature, media sources, and academic studies from 2013 to 2025. The analysis is guided by Dunlap’s framework of green extractivism. The findings show that IMIP reflects four interrelated features of green extractivism. Climate crisis and energy transition narratives are used to justify rapid industrial expansion. Extractive activities are legitimized through sustainability claims such as green development, ESG, and decarbonization. Downstreaming remains dependent on conventional extractivism, including upstream mining, land conversion, and coal-based energy systems. Sustainability is framed as a manageable technical issue, while socioecological impacts continue to accumulate, including environmental degradation, health risks, and livelihood disruption. This article contributes by extending the analysis of green extractivism beyond Latin America and by showing how it operates through a state-led downstreaming and industrial park model. It demonstrates that sustainability narratives can function as a justification for extractive expansion, raising concern about the conditions under which green industrialization can be aligned with meaningful environmental and social outcomes.